Significant Developments in Local School Systems : Ontario's Educative Society, Volume VI - Fleming, W. G. (Book collections on Project MUSE., 1972)
This volume deals with innovative developments of many different kinds in the local school systems in the years up to 1970. Information was obtained from a sampling of school boards, including the largest. The major purpose is to show what may be expected from an educational organization that gives local authorities a certain amount of leeway to depart from standard procedures. Innovations in teaching, curricular experimentation, changes in the structure and use of school buildings, and the growth of special services are fully covered.